EXAMINING THE COMMODIFICATION OF POVERTY NEWS: A CASE STUDY OF KOMPAS TV’S WEBSITE, MARCH 2022 - Adhrianti, Lisa; Eka Vuspa Sari; M. Hik Wahyuda (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Discussing poverty in the media is intriguing, as every broadcast on the subject has the potential to evoke empathy and sympathy from the public. Additionally, commodification refers to transforming the value of a product that previously held only use value into a marketable value. This qualitative descriptive research aimed to examine the commodification of poverty presented by Kompas TV in March 2022. To collect data, observation, and documentation of poverty-related news on Kompas TV were conducted, along with interviews with communication experts and journalists. Subsequently, the collected data underwent qualitative processing and analysis to achieve the research objectives. This study yielded the following results: 1) Two forms of commodification were identified in the March 2022 edition of Kompas TV's poverty news, content commodification and immanent commodification. 2) The commodification observed occurs across three stages of television news production: the news gathering stage, the news production stage, and the news presentation stage. 3) Content commodification takes place in two stages of television news production, which are the news gathering stage and the news production stage. This is evident in the selection of topics, points of view, dramatic shooting, grouping of types of news, script editing, and video and sound editing. 4) Immanent commodification is identified at the news presentation stage, involving the production of new commodities derived from previous commodities. Furthermore, the research results lead to the following suggestions: 1) Encourage the media to prioritize poverty news, ensuring that the issue of poverty consistently occupies a prominent place in public discourse 2) Advocate for the media to amplify the voices of the poor by presenting them as individuals experiencing poverty from a human standpoint